2022
DOI: 10.1149/2162-8777/ac56c2
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Driven Optical, Electronic, and Mechanical Properties of Inorganic Halide Perovskite CsGeBr3

Abstract: Of late, inorganic perovskite material, especially the lead-free CsGeBr3, has gained considerable interest in the green photovoltaic industry due to its outstanding optoelectronic, thermal, and elastic properties. In this work, we systematically investigated the strain-driven optical, electronic, and mechanical properties of CsGeBr3 through the first-principles density functional theory. The unstrained planar CsGeBr3 compound demonstrates a direct bandgap of 0.92 eV at its R-point. However, by incorporating ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…and the maximum force endurance below 0.01 eV/Å. [45,46] During the relaxation studies for ionic and structural adjustment, a limit of 10 −3 a. u. was set for the level of force convergence that was deemed acceptable. Giannozzi et al [43] employed LDA and GGA functionals to compute specific organic halides, and determined that the absolute average error exceeds 10 pm.…”
Section: Methodsmentioning
confidence: 99%
“…and the maximum force endurance below 0.01 eV/Å. [45,46] During the relaxation studies for ionic and structural adjustment, a limit of 10 −3 a. u. was set for the level of force convergence that was deemed acceptable. Giannozzi et al [43] employed LDA and GGA functionals to compute specific organic halides, and determined that the absolute average error exceeds 10 pm.…”
Section: Methodsmentioning
confidence: 99%
“…The optical properties of a superconducting substance are attractive due to its remarkable nature. They show promising results in photovoltaics and optoelectronics. , This section investigates and provides a detailed analysis of a few optical characteristics. The results are shown at pressures of 0–10 GPa for LiGa 2 Ir.…”
Section: Resultsmentioning
confidence: 99%
“…It is feasible to ascertain if a material is ductile (+ve/positive value) or brittle (−ve/negative value), employing the Cauchy pressure (C 11 − C 44 ). 23,26 In Table 3, the estimated Cauchy pressure is tabulated, and it can be observed that both compounds' computed values are positive under all applied stresses, revealing that they are ductile. With heightened pressure, materials become more ductile (see Table 3).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations